If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + -2x = 43x + 16 Reorder the terms: 86 + -2x = 16 + 43x Solving 86 + -2x = 16 + 43x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-43x' to each side of the equation. 86 + -2x + -43x = 16 + 43x + -43x Combine like terms: -2x + -43x = -45x 86 + -45x = 16 + 43x + -43x Combine like terms: 43x + -43x = 0 86 + -45x = 16 + 0 86 + -45x = 16 Add '-86' to each side of the equation. 86 + -86 + -45x = 16 + -86 Combine like terms: 86 + -86 = 0 0 + -45x = 16 + -86 -45x = 16 + -86 Combine like terms: 16 + -86 = -70 -45x = -70 Divide each side by '-45'. x = 1.555555556 Simplifying x = 1.555555556
| 7-x=28 | | 5(10x-10)=200 | | 7.9z-6.9z-2.4=-5.2 | | (10x-20)=-80 | | (10x-2n)=-80 | | 0=4x-4+5x-5 | | n+(n+1)+(n+2)=96 | | 3.9y-2.8=6.7 | | x/4=3 | | 11x-4=4x+10 | | x^3-7x^2=-5x-35 | | 6-2(y-3)=24 | | 3a^3-5a^2+2=0 | | x+6=23 | | -4y-2=-(4y+2) | | 4x+2+5x-3=6x-4-7x+5 | | -4y-7=-7y+11 | | 40-y=5-y | | x^2+y^2-6x-8x+16=0 | | 3x^2-2x-7= | | 15=u-1 | | s+(-29)=51 | | 5x+10=17x-14 | | d-(-49)=67 | | 3(y-7)=48 | | y-(-26)=87 | | g+(-39)=-68 | | -.1x^2+27x-400=0 | | 91-6x=21x+22 | | f-(-2)=9 | | x-8y=7 | | t-(-3.4)=-5.3 |